ANALISIS FAKTOR – FAKTOR PENGHAMBAT GURU DALAM MATERI TANGGUNG JAWAB, HAK, DAN KEWAJIBAN PADA SISWA SLOW LEARNER - Mubarokah, Viya Zakiyatul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This research discusses the inhibiting factors of teachers in the subject of responsibility, rights, and obligations of slow learner students. Aims to find out in general the results of the implementation of learning and the factors that hinder the teacher in Theme 2 of the Responsibility, Rights and Obligations of Slow Learner students. Using this type of qualitative descriptive research, namely research that uses problem solving with existing data. The subjects of this study were class teachers, special companion teachers (GPK), and one of the slow learner students with observations and interviews, research was carried out in the Covid19 pandemic era by implementing health protocols. Based on the results of research, the implementation of learning carried out at SDN Gedangan has not fully provided the same learning between regular students and Slow Learner students. The lack of GPK assistance for Slow Learner students is due to only 1 week 2 times, and in closing activities the teacher only conducts evaluation and further actions without repeating the material that has been given.